1971
DOI: 10.1044/jshr.1403.618
|View full text |Cite
|
Sign up to set email alerts
|

Monaural/Binaural Minimum Audible Angles for a Moving Sound Source

Abstract: Papers on monaural localization relating to the action of the vestibular apparatus, influence of the auricle, and movements of the head were reviewed. To test one conclusion of the review, that a moving sound source should yield a continuous set of changing loudness/phase/timing cues available to the ear, an experiment was conducted which provides more complete quantification of monaural/binaural comparison. Minimum audible angles (maa) were computed from the responses of three men, highly experienced in liste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 0 publications
5
39
1
Order By: Relevance
“…showed an elevated final MAMA (4.0°) relative to her initial MAMA (3.1°), although a matched t test revealed that the difference was only of borderline significance (p = .06).4 For all subjects, the initial unadapted MAMA was very nearly the same as the MAMA determined with the 0°/sec adaptor (averages: 2.6°and 2.4°, respectively). These values are in general agreement with previously reported MAMAs determined under similar conditions (Chandler & Grantham, 1992;Grantham, 1986;Harris & Sergeant, 1971;Perrott & Marlborough, 1989).…”
Section: Resultssupporting
confidence: 82%
“…showed an elevated final MAMA (4.0°) relative to her initial MAMA (3.1°), although a matched t test revealed that the difference was only of borderline significance (p = .06).4 For all subjects, the initial unadapted MAMA was very nearly the same as the MAMA determined with the 0°/sec adaptor (averages: 2.6°and 2.4°, respectively). These values are in general agreement with previously reported MAMAs determined under similar conditions (Chandler & Grantham, 1992;Grantham, 1986;Harris & Sergeant, 1971;Perrott & Marlborough, 1989).…”
Section: Resultssupporting
confidence: 82%
“…The MAMA is usually larger than the MAA, typically twice as large, for the same sound source and the same initial (reference) direction and is independent of direction of movement in the horizontal plane (e.g., Chandler and Grantham, 1992;Grantham et al, 2003;Perrott and Musicant, 1977) and signal intensity (Perrott and Marlborough, 1989). Similarly to the MAA, the MAMA is smallest in front of the listener and increases as the sound source moves away from the listener laterally (Harris and Sergeant, 1971;Grantham, 1986); is smaller for wide-than narrow-band stimuli (Harris and Sergeant, 1971;Saberi and Perrot, 1990); and is largest in the mid-high frequency range (Perrott and Tucker, 1988). In general, MAMAs are U-shaped functions of velocity, with optimum resolution obtained at about 8°-16°/s in the horizontal plane and 7°-10°/s in the vertical plane .…”
Section: Perception Of Moving Sound Sourcesmentioning
confidence: 99%
“…Although the classic paper by Stevens and Newman (1936) reported that tones around 2,000-4,000 Hz are localized less precisely than tones of lower (or higher) frequency, more recent studies have revealed that this frequency effect is small or negligible, especially in the region around midline (Harris & Sergeant, 1971;Mills, 1958;Molino, 1974;Sandel, Teas, Fedderson, & Jeffress, 1955).…”
Section: Notesmentioning
confidence: 99%